Dasboard Monitoring Mahasiswa Dan Lulusan Untuk Meningkatkan Potensi Penerimaan Mahasiswa Baru Serta Strategi Pemasaran - Leo Putrawan Handho; Susan Dian Purnamasari (Journal of Computer and Information Systems Ampera, 2020)
In the development of information technology today, information technology can be used in various aspects of the world of work to help and facilitate the work, one of which is in the field of education or academic. One example is at a university. The university is very important in looking at and monitoring the performance of its students and graduates, to support the need for information quickly and up to date on various business processes, so that executives at a university can see the development and analyze the data well. This research will use the science of information technology namely business intelligence by using the OLAP (Online Analyctical Processing) method that there are stages in it, among others, Analysis Services Project, Integration Service Project, and Reportin. This research was designed with a monitoring system through a dashboard. This dashboard with a Business Intelligence perspective not only dynamically monitors, but also provides predictive results information to support decisions for executives at a university